Survei Proses Pembelajaran Pendidikan Jasmani di Masa Pandemi Covid-19 di SMA Negeri Se-Kabupaten Boyolali - Muhammad Hazairin Zain Mukhtarom; Rumini Rumini (Indonesian Journal for Physical Education and Sport, 2022)
The purpose of this study was to find out the right process for physical education subjects at State Senior High Schools throughout Boyolali Regency during the Covid-19 pandemic. This research is a type of qualitative research with a descriptive approach. The object of this research is the physical education learning process during the COVID-19 pandemic at State Senior High Schools in Boyolali Regency. The data used in this study are primary data and secondary data. The data was obtained through the process of observation, interviews, and documentation. The analysis used is data reduction, data presentation, and conclusion drawing. The results of the research are learning planning strategies are carried out using strategies in making syllabus andlesson plans blended, learning implementation strategies are carried out in asynchronous transfer mode and asynchronous learning, and assessment strategies are carried out through three aspects, namely affective, cognitive, and psychomotor aspects. The conclusion of this research is that the physical education learning strategy during the covid-19 pandemic at SMA Negeri Boyolali is quite good, although it still looks like it has not been implemented effectively due to certain obstacles.